VARRO, ATTICUS, AND ANNALES. (12th December 2017) - MARSHALL, R. M. A.
Abstract: This paper explores the scholarly relationship between Varro and Atticus by focusing on the attribution of a Varronian fragment (Gell. 17.21.24). Taking into account Gellius's citation practices, it is argued that the fragment (concerning the execution of the tyrant Manlius) was mediated via Atticus, not taken directly from Varro. The evidence for Varro's and Atticus's friendship and scholarly cooperation undermines traditional attempts to identify any ultimate written source for this material, and prompts a re-evaluation of the relationship between the two friends' antiquarian interests to outline the consequences of scholarly and social exchange. This investigation suggests that, like many apparent points of Attico-Varronian overlap (including Rome's foundation-date), the fragment's origins might owe more to personal acquaintance than secluded book-learning. Their antiquarian choices had the potential to be politically charged, and the version of Manlius's death endorsed by Varro may thus indicate his political stance towards Caesar.